Bond indenture consent solicitations as a debt management tool - Jamie A. Anderson-Parson; Terrill R. Keasler; Robin T. Byerly (International Journal of Financial Studies, 2015)
Many companies in recent years are seeking new ways to manage their debt liabilities. Companies with outstanding debt securities can engage in a variety of transactions with bond holders. Choices will depend to some extent on whether or not the company has access to cash and is able to purchase in the open market or through cash tender offer, or if without cash, by making an exchange offer of new securities for existing securities. Often in either case, there is a bond indenture consent solicitation needed to waive or amend existing bond terms, the announcement of which signals management's intent to the market. Given the increasing prevalence of this practice as a debt management tool, this study seeks to determine whether it is truly perceived to be value enhancing by stockholders. Using an event study of 50 companies announcing bond indenture consent solicitations, we find that shareholders do benefit, and companies appear well served by this practice.
Keywords: G32; 330; bond indenture consent solicitations; bondholder coercion; debt risk management